PENINGKATAN HASIL BELAJAR SHOOTING BOLA BASKET MENGGUNAKAN MEDIA AUDIOVISUAL PADA PESERTA DIDIK SMA NEGERI 1 SUNGAI RAYA - Dian Supatri; Fitriana Puspa Hidasari; Mimi Haetami (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThe problem of this research is that students do not understand the basic technique of basketball, namely shooting, students cannot shoot basketball correctly and students cannot understand the material presented by the physical education teacher. This research is a classroom action research. First cycle and the second cycle. As in the cycle, there are steps the researcher takes, namely planning, acting, observing and reflecting. In this study, the subjects used were students of class XI MIA 3 at SMA Negeri 1 Sungai Raya which were taken from the cluster sampling method and the instrument used in this study was the rubric for the assessment of the basketball shooting test results. The results of the research obtained from students where it can be seen that those who got a score above the KKM in cycle I were 47.12% or as many as 17 students, then increased in cycle II by 72.22% or as many as 26 students. This classroom action research stopped in the second cycle because 75% of the research success indicators had been achieved.Keywords: learnings, shooting, audiovisual